2014
DOI: 10.1086/678693
|View full text |Cite
|
Sign up to set email alerts
|

Selective feeding determines patterns of nutrient release by stream invertebrates

Abstract: One common stoichiometric approach to predicting patterns of nutrient release (excretion + egestion) by animals in aquatic ecosystems is to base predictions on elemental mass-balance constrained by homeostatic maintenance. An easily measured resource composite (i.e., seston, epilithon, or leaf litter) often is used to represent ingested stoichiometry, but whether such a composite is a good indicator of food actually ingested is a relatively unexplored assumption. We examined the application of a stoichiometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 64 publications
2
34
0
Order By: Relevance
“…We provide robust support for previous findings and our first predictions (P1 and P2) regarding diet and taxonomic variation in egesta nutrient content (Patrick ; Hood et al . ; Halvorson et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We provide robust support for previous findings and our first predictions (P1 and P2) regarding diet and taxonomic variation in egesta nutrient content (Patrick ; Hood et al . ; Halvorson et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…) and shredder egesta are often more N and P rich than detrital food resources (Hood et al . ; Halvorson et al . ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, some studies found high consumption of low-nutrient leaf litter, indicating compensatory feeding on low-quality food (Danger et al, 2013a;Flores et al, 2014). When evaluating these discrepancies, we must keep in mind that leaf-shredding detritivores selectively feed on locally enriched patches of overall nutrient-impoverished litter (Arsuffi and Suberkropp, 1985;Lauridsen et al, 2014;Hood et al, 2014). An important implication is that apparent stoichiometric imbalances of bulk litter can be overcome, potentially leading to counterintuitive consumption rates, consumer-mediated nutrient recycling, and changes in elemental concentrations of the remaining litter (Fig 1).…”
Section: Consequences For Consumersmentioning
confidence: 99%
“…Leaf litter conditioned by fungi is preferentially consumed by detritivores, with consumptions rates being influenced by leaf litter quality (Irons et al, 1988;Schlief and Mutz, 2006;B€ arlocher and Sridhar, 2014) and probably by stoichiometric requirements of the detritivores. Finally, leaf litter consumption can lead to changes in litter stoichiometry through selective feeding on nutrient-rich leaf patches (Lauridsen et al, 2014), which in turn influences rates of consumer-driven nutrient cycling (Hood et al, 2014) …”
Section: Fungal and Bacterial Susceptibility To N Limitationmentioning
confidence: 99%